DETECTING GENDER’S STRATEGIES IN LEARNING SPEAKING - Adelina Anum; Sigit Apriyanto (Premise: Journal of English Education and Applied Linguistics, 2019)
The researchers intended to know what strategies were used by male and female students in learning speaking, especially at the tenth grade of SMKN Karangpucung and what dominant strategy was used by male and female students in learning speaking. The main question to be answered in this research was concerned with the strategy used by male and female students and what the dominant strategy used by male and female students. The population in this research were 320 students at the tenth grade of SMKN Karangpucung consisting of automotive and accountancy programs, and 32 students were taken as the sample. The instrument used to collect data was a questionnaire consisting of 30 questions to determine the students' strategies used by every male and female student. This research showed that male students tended to use metacognitive strategies and female students tended to use affective strategies. Therefore, the researchers concluded that metacognitive strategies are more likely to be used by male students and affective strategies are more likely to be used by women students. Surprisingly, metacognitive strategies were dominated by male students, while affective strategies were dominated by female students.